Single and multiple dose pharmacokinetics of maritime pine bark extract (Pycnogenol) after oral administration to healthy volunteers - Grimm, Tanja (BioMed Central, 2006)
BACKGROUND: Since plant extracts are increasingly used as phytotherapeutics or dietary supplements information on bioavailability, bioefficacy and safety are warranted. We elucidated the plasma kinetics of genuine extract components and metabolites after single and multiple ingestion of the standardized maritime pine bark extract Pycnogenol (USP quality) by human volunteers. METHODS: Eleven volunteers received a single dose of 300 mg pine bark extract, five volunteers ingested 200 mg daily for five days to reach steady state concentrations. Plasma samples were obtained before and at defined time points after intake of the extract. Samples were analyzed by HPLC with ion-pair reagents and simultaneous UV and electrochemical detection. RESULTS: We quantified total plasma concentrations of catechin, caffeic acid, ferulic acid, taxifolin and the metabolite M1 (δ-(3,4-dihydroxy-phenyl)-γ-valerolactone). Additionally, we describe plasma time courses and steady state appearance of ten so far unknown compounds, U1 to U10. After single ingestion, compounds derived from the extract were rapidly absorbed and the majority of them were detectable over whole experimental period of 14 h. The analysis of steady state plasma samples revealed significant phase II metabolism. CONCLUSION: We present the first systematic pharmacokinetic analysis of compounds derived from maritime pine bark extract. Beyond the known constituents and metabolites we uncovered the plasma time courses of ten unknown compounds. In concert with our previous detection of anti-inflammatory bioefficacy of these plasma samples ex vivo we suggest that constituents and metabolites of Pycnogenol bear potential for disclosure of novel active principles.